2020
DOI: 10.3329/ralf.v7i3.51363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imidacloprid-Contaminated Feed Exposure on Hematological Parameters in Adult Rabbits (Oryctolagus Cuniculus)

Abstract: Blood parameters are an important index to assess the body homeostasis in mammals. Here, the effect of pesticide (imidacloprid) contaminated feed exposure on the haematological parameters of adult rabbits (n=15) was studied. Pesticides (Imidacloprid, Bildor® 0.5ml (100mg)/L water spray on vegetables and green grass) exposed feed fed to rabbits with wash (washed feed rabbit) or without a wash (not washed feed rabbit) in the once-daily morning for every alternative day up to 15 days. Control rabbits have receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous findings have shown that oxidative stress responds to exposure to RF-EMR ( Consales et al, 2012 , Yüksel et al, 2016 , Yurekli et al, 2006 ). Oxidants could interrupt cellular membrane enzyme activity, impair cellular activities, and perhaps lead to cell death ( Achudume et al, 2012 , Hasan et al, 2021b , Karim et al, 2020 , Kobir et al, 2020 ). Most noticeable behavioral and cognitive disorders of the central nervous system identified in both people and animals regarding long-term smartphone radiation exposure ( Babadi-Akashe et al, 2014 , Söderqvist et al, 2015 , Zhao et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have shown that oxidative stress responds to exposure to RF-EMR ( Consales et al, 2012 , Yüksel et al, 2016 , Yurekli et al, 2006 ). Oxidants could interrupt cellular membrane enzyme activity, impair cellular activities, and perhaps lead to cell death ( Achudume et al, 2012 , Hasan et al, 2021b , Karim et al, 2020 , Kobir et al, 2020 ). Most noticeable behavioral and cognitive disorders of the central nervous system identified in both people and animals regarding long-term smartphone radiation exposure ( Babadi-Akashe et al, 2014 , Söderqvist et al, 2015 , Zhao et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the excess amount of use of antibiotics in farm areas is increasing the number of MDR organisms. It has been found that pesticide residue, which is used for agricultural purposes, may affect the body homeostasis of animals (Kobir et al, 2020).…”
Section: Resultsmentioning
confidence: 99%